2009
DOI: 10.1109/tap.2009.2029299
|View full text |Cite
|
Sign up to set email alerts
|

Low-Profile Directive Millimeter-Wave Antennas Using Free-Formed Three-Dimensional (3-D) Electromagnetic Bandgap Structures

Abstract: We present design methodologies for directive millimeter-wave antennas using free-formed three-dimensional (3-D) electromagnetic bandgap (EBG) structures. Dispersion characteristics of 3-D EBGs have been computed by finite-difference time-domain (FDTD) simulations and the designed EBGs have been fabricated by using the extrusion free-forming technique. The fabricated EBG structures have been measured and integrated with a waveguide feed to form a Fabry-Perot cavity antenna. The prototype antenna demonstrated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…From our study, we found that the proper structure of EBG is capable to enhance the gain of antenna as the additional resonant circuit which installed at front of the array panel. Furthermore, the EBG structures can be appropriately shaped for reducing the side and back lobes of the directional antenna too [17] [18]. From investigation, the sector of cylindrical woodpile EBG structures [19] are more suitable for the antenna type B.…”
Section: Ebg Configurationmentioning
confidence: 99%
“…From our study, we found that the proper structure of EBG is capable to enhance the gain of antenna as the additional resonant circuit which installed at front of the array panel. Furthermore, the EBG structures can be appropriately shaped for reducing the side and back lobes of the directional antenna too [17] [18]. From investigation, the sector of cylindrical woodpile EBG structures [19] are more suitable for the antenna type B.…”
Section: Ebg Configurationmentioning
confidence: 99%